Age-specific response of skeletal muscle extracellular matrix to acute resistance exercise: A pilot study. Issue 3 (16th March 2019) - Wessner, Barbara; Liebensteiner, Michael; Nachbauer, Werner; Csapo, Robert
Abstract: The extracellular matrix (ECM) plays an essential role in the development, growth and repair of skeletal muscles and serves to transmit contractile force. However, its regulation is poorly understood. This study investigates the age-specificity of the effects of acute resistance exercise on ECM gene expression. To this purpose, five young (YM, 23.8 ± 2.2 yrs.) and 5 elderly (EM, 66.8 ± 4.1 yrs.) men performed one session of unilateral leg press and leg extension exercises. Six hours post-exercise, biopsies were taken from the vastus lateralis muscles of both legs. A PCR array was used to profile the expression of 84 ECM-related genes, of which 6 were validated by qPCR. The PCR array found 9 and 4 ECM-associated genes to be selectively altered (>1.5-fold change) in YM or EM only. Four further genes were upregulated in YM but downregulated in EM. Of the 6 genes validated on individual samples MMP9 expression increased in YM (9.7-fold) and decreased (0.2-fold) in EM. MMP15 was downregulated in EM only (0.6-fold). A significant correlation between leg extension 1 RM and changes in COL7A1 expression ( ρ  = 0.71) suggests a potential influence of fitness levels. In conclusion, acute resistance exercise affects ECM gene expression at least partly in an age-specific manner. The altered expression of genes encoding matrix metalloproteinases (MMP3, MMP9, MMP15) highlights the role of remodelling processes in the response to an acute bout of resistance exercise. Larger studies are required to verify the age-associated differences in gene expression profiles and establish their functional implications.